(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
Through the maritime geographical space that the Greeks made the process of migration to the different regions bathed by sea throughout the Aegean, Mediterranean and Black Sea, founded new poleis, carried out a shared identity, transferred their cults and gods, produced ceramic and metal artifacts forming the net Of maritime connectivity through emporium and apoikias.